2008
DOI: 10.1039/b718367d
|View full text |Cite
|
Sign up to set email alerts
|

Framework functionalisation triggers metal complex binding

Abstract: Post-synthetic derivatisation of a porous material produces a functionalized material that binds the metal complex V(O)acac2, in contrast to the unfunctionalized precursor, which is inactive for complex binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
154
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(171 citation statements)
references
References 21 publications
(27 reference statements)
3
154
0
7
Order By: Relevance
“…The authors carried out a preliminary catalytic investigation on this modified MOF structure for the oxidation of cyclohexene with TBHP as the oxidant. However, the VO(acac) 2 @IRMOF-3 showed a rather low catalytic activity and stability 104 . The group of Ahn reported a more straightforward one step functionalization of the IRMOF-3 with a manganese complex (entry 21 Table 4) 105 .…”
Section: Pom@mofmentioning
confidence: 95%
See 1 more Smart Citation
“…The authors carried out a preliminary catalytic investigation on this modified MOF structure for the oxidation of cyclohexene with TBHP as the oxidant. However, the VO(acac) 2 @IRMOF-3 showed a rather low catalytic activity and stability 104 . The group of Ahn reported a more straightforward one step functionalization of the IRMOF-3 with a manganese complex (entry 21 Table 4) 105 .…”
Section: Pom@mofmentioning
confidence: 95%
“…A similar mechanism was proposed (Scheme 7) with the generation of phthalimide N-oxyl radicals acting as precursors of C-centered radicals that would undergo auto-oxidation. Ingleson et al 104 reported the two steps modification of IRMOF-3 to an imine grafted VO(acac) 2 complex (entry 20 Table 4). The authors carried out a preliminary catalytic investigation on this modified MOF structure for the oxidation of cyclohexene with TBHP as the oxidant.…”
Section: Pom@mofmentioning
confidence: 99%
“…14 In addition, functionalization with aromatic -NH 2 groups may facilitate metal complex binding, as demonstrated by M. J. Ingleson et al 15 However, the utilization of these functionalized MOFs as catalysts in the dehydrogenation of AB aqueous solution has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, three different ways are used for the functionalisation: (1) functional groups (e.g. -NH 2 , -NO 2 , -N 3 ) react with another reactive molecule inside the pores, [20][21][22][23][24] (2) coordinative unsaturated sites are used, 25 and (3) nucleophilic substitution takes place at the aromatic ring. 26 Important requirements for the post-synthetic modification are a high chemical stability and large, accessible pores of the host material.…”
Section: Introductionmentioning
confidence: 99%